The Effectiveness of Oil Palm Empty Fruit Bunch Growing Media and Liquid Organic Fertilizer on the Production of Pakcoy Mustard (Brassica rapa) in a Hydroponic System - Reza Andry Prabowo; Najla Lubis; Desi Sri Pasca Sari Sembiring (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2026)
The study was conducted to determine the effectiveness of planting media and liquid organic fertilizer on the production of pakcoy mustard in a hydroponic system. Using a factorial Completely Randomized Design (RAL) method. The first factor of planting media consisted of four levels: M1: TKKS, M2: TKKS+cocopeat (75:25), M3: TKKS+cocopeat (50:50), M4: TKKS+cocopeat (25:75). The second factor of liquid organic fertilizer consisted of four levels: K1: AB Mix, K2: POC 10%, K3: POC 15%, K4: POC 20%. The total treatment was 16 combinations and 32 experimental units. The results of statistical tests showed that the combination of planting media and liquid organic fertilizer from fruit waste had no significant effect on plant height and number of leaves, but had a very significant effect on leaf width, leaf length, leaf area, sample weight, and weight per plot. In addition to the control treatment, the use of TKKS+cocopeat (75:25) planting media and 10% POC provided the best results, thus potentially increasing pak choy mustard production.